Murals and Prints of St. John of Rila and the Revival Pilgrimage - Mihailov, Plamen (Forum Theologicum Sardicense, 2025)
Plamen Mihailov, Murals and Prints of St. John of Rila and the Revival Pilgrimage. The Orthodox pilgrimage in Bulgaria is strongly connected with the most revered saints among the local Christians. In the times of Ottoman empire, when open confession of the faith was difficult, the icons and murals in the churches were silent and immortal testimonies to the masses about the life and the sacrifice of the saints. This article examines the life of St. John of Rila and his depiction in the Bulgarian churches and monasteries – his earliest images, his life scenes in the Revival murals and the prints of the Rila Monastery for pilgrims.